The Impact of Fair Performance Appraisal to Employee Motivation and Satisfaction towards Performance Appraisal â A Case of PT. XYZ. - Cowandy, Christian Jonathan (iBuss Management, 2014)
This research is conducted to find out employeesâÂ  perception about their performance appraisal system at PT. XYZ. The perception will be about how fair is the performance appraisal system of PT. XYZ, and how it can affect the employeesâ motivation and their satisfaction towards the performance appraisal system itself.This research is conducted in PT. XYZâs headquarter in Surabaya by distributing questionnaire to 80 employees of PT. XYZ from various different functions in the company. The data was analyzed using Multiple Linear Regression Analysis. The results shows that fair performance appraisal have significant impact on employeesâ motivation to improve performance and satisfaction towards performance appraisal. Individually, all factors of fair performance appraisal have significant impact to employeeâsÂ  motivation, but for satisfaction towards performance appraisal, only procedure fairness has significant impact to satisfaction towards performance appraisal. Â Keywords: Human Resources, Motivation, Employeeâs Motivation, Satisfaction towards Performance Appraisal, Performance Appraisal